1998
DOI: 10.1152/jappl.1998.85.3.830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide synthase inhibition on cutaneous vasodilation during body heating in humans

Abstract: We sought to examine further the potential role of nitric oxide (NO) in the neurally mediated cutaneous vasodilation in nonacral skin during body heating in humans. Six subjects were heated with a water-perfused suit while cutaneous blood flow was measured by using laser-Doppler flowmeters placed on both forearms. The NO synthase inhibitor NG-monomethyl-L-arginine (L-NMMA) was given selectively to one forearm via a brachial artery catheter after marked cutaneous vasodilation had been established. During body h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
150
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 22 publications
11
150
1
Order By: Relevance
“…Results also contrast with those of Binggeli et al (3) who found that aspirin reduced rather than increased RH flow. Some of the differences of our study from these other studies may be due to our use of locally delivered Keto versus the use of systemically administered PG inhibitors in the other studies (28,29). Systemic administration may exert potential generalized effects indirectly affecting peripheral blood flow.…”
Section: Comparison With the Literaturementioning
confidence: 85%
See 2 more Smart Citations
“…Results also contrast with those of Binggeli et al (3) who found that aspirin reduced rather than increased RH flow. Some of the differences of our study from these other studies may be due to our use of locally delivered Keto versus the use of systemically administered PG inhibitors in the other studies (28,29). Systemic administration may exert potential generalized effects indirectly affecting peripheral blood flow.…”
Section: Comparison With the Literaturementioning
confidence: 85%
“…Thus whereas Larkin and Williams (20) studying laser-Doppler measurements of skin blood flow showed that RH in the human forearm is mediated by a local reflex involving sensory nerves and a cyclooxygenase (COX) product, showed that there was no significant response to acute systemic COX inhibitors. However, the systemic administration of drugs does not always produce an adequate blockade in the skin (28,29).NO, NOS isoforms, and COX products mutually interact since there is increasing evidence suggesting considerable "cross talk" between NO and PG biosynthetic pathways involving an active back modulation operated by reaction end products, including NO, PGs, and cyclic nucleotides (22). For example, thromboxane A 2 exerts inhibitory effects on bioavailable NO through increasing oxidative stress (32) and inhibiting NOS (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that production, release, and vascular responsiveness to nitric oxide is abnormal in patients with CHF, [37][38][39][40] whereas studies have shown that Ϸ30% of the elevation in cutaneous vascular conductance during indirect whole-body heating is mediated by nitric oxide-dependent mechanisms. 41,42 Therefore, if nitric oxide production, release, and/or responsiveness are similarly attenuated in the skin of patients with CHF, this could explain a component of the observed reduction in cutaneous vasodilation during the whole-body heat stress.…”
Section: Cui Et Al Thermal Regulatory Responses In Chf 2289mentioning
confidence: 99%
“…Physiological mechanisms contributing to the disproportionate temporal progression of sudomotor and vasomotor dysfunction with age remain unclear. Furthermore, despite attempts to identify a putative signaling pathway or cotransmitter relating the two responses, including speculation over VIP (40), bradykinin (4), and nitric oxide (33), a single mechanism has not yet been elucidated. The regional progression of age-related vasomotor and sudomotor dysfunction is not well characterized, with limited vasomotor data available and conflicting results of regional sudomotor adjustments.…”
mentioning
confidence: 99%